A Simple Method for Making Diagnostic Casts for Dental Implants Using Acrylic Abutments - H. Siadat; A. Shahrokhi Rad; A. Mirfazaelian (Tehran University of Medical Sciences, 2007)
The use of multiple implants in the same jaw requires a detailed knowledge of abutment angulation. The position and angulation of the abutments play an important role in treatment planning and fabrication of the custom tray. Therefore diagnostic casts that contain cover screws may cause problems during implant therapy. The current article describes a technique for making a preliminary cast with acrylic custom abutments in order to help the clinician select an appropriate impression technique and evaluate the location and angulations of the implant bodies. This method can also aid the technician to provide adequate and proper space for the fabrication of an open custom tray.